Recurrent Squamous Cell Carcinoma Arising from Ovarian Mature Cystic Teratoma with Cardiac Metastases: A Case Report - Cai, Lixia; Wang, Ling; Chen, Xiangyu; Zheng, Zhelan (Archives of Clinical and Medical Case Reports, 2022)
Introduction: Mature Cystic Teratoma (MCT) is a common ovarian germ cell tumor, the secondary development of malignancy in MCT is rare. Squamous-Cell Carcinoma (SCC) accounts for 80% of secondary malignant transformations of MCT (SCC-MCT). SCC-MCT with cardiac metastases is extremely rare. Patient concerns: we report a 35-year-old Chinese woman who chose to undergo fertility sparing surgery due to her second childbirth needs. 2 years later, SCC-MCT recurred with cardiac metastases. Diagnoses: Postoperative pathology confirmed that the cardiac tumor was poorly differentiated squamous cell carcinoma derived from the ovary. Interventions: Patient underwent chemotherapy after cardiac tumor resection. Outcomes: Patient requested to be discharged after chemotherapy, no follow-up information available. Lessons: Due to the difficulty of preoperative diagnosis and poor prognosis, it is necessary to be cautious when choosing fertility-sparing surgery for SCC-MCT.